Alternative Dispute Resolution dalam Mediasi Sengketa Hukum Adat Di Papua - Alexander Alexander (Jurnal Syntax Transformation, 2021)
The existence of tribes, not only must be accepted and respected as a sociological and historical reality, but must also be maintained and maintained to realize a goal because it is not uncommon for conflicts between tribes to occur, especially in indigenous Papuan blood. This is important for the creation of an atmosphere of community life that is full of tolerance, tolerance, and harmony. Disputes can be resolved in two ways, namely through state courts (litigation) and out-of-court dispute resolution (nonlitigation). The purpose of this study is to find out the Alternative Dispute Resolution in the mediation of customary legal disputes in Papua case study in Jayawijaya Police. Normative juridical research methods are also called doctrinal research, empirical juridical research is called non-doctrinal. The results of this study show that non-litigation settlements are chosen by the community on the grounds that relatively faster time can be realized, low cost and settlement of problems is done by peaceful means, namely through deliberation. Historically, Indonesian culture has strongly upheld the costensus approach, but sometimes it is less effective that the development of ADR in Indonesia seems to be stronger than the reasons for the inefficiency of the judicial process. The process of completion through ADR is not a new in the cultural values of our cooperative nation. In terms of resolving the type of delik that is considered heavy, then indigenous peoples cooperate with the police to solve it.